2021
DOI: 10.1136/jnnp-2020-325549
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation predicts disease progression in progressive supranuclear palsy

Abstract: IntroductionIn addition to tau pathology and neuronal loss, neuroinflammation occurs in progressive supranuclear palsy (PSP). However, the prognostic value of the in vivo imaging markers for these processes in PSP remains unclear. We test the primary hypothesis that baseline in vivo imaging assessment of neuroinflammation in subcortical regions predicts clinical progression in patients with PSP.MethodsSeventeen patients with PSP–Richardson’s syndrome underwent a baseline multimodal imaging assessment, includin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 45 publications
4
25
2
Order By: Relevance
“…In other words, in areas with relatively low tau accumulation synaptic density is minimally affected, whereas in areas with higher tau accumulation there is reduction of synaptic density as the disease progresses and this preferentially occurs in synapse rich areas. As the disease progresses, other pathological processes may contribute to synaptic loss, such as inflammation, another predictor of prognosis and mediator of synaptic loss 46 . There is therefore not a simple linear relationship between tau accumulation and synaptic density in moderate and advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, in areas with relatively low tau accumulation synaptic density is minimally affected, whereas in areas with higher tau accumulation there is reduction of synaptic density as the disease progresses and this preferentially occurs in synapse rich areas. As the disease progresses, other pathological processes may contribute to synaptic loss, such as inflammation, another predictor of prognosis and mediator of synaptic loss 46 . There is therefore not a simple linear relationship between tau accumulation and synaptic density in moderate and advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical TSPO imaging studies, no evidence with respect to rs6971 polymorphisms has been reported. Microglia activation assessed by using [ 11 C]PK11195 PET was reported to co-localize with tau and can predict disease progression and tau accumulation assessed by [ 18 F]flortaucipir in patients with PSP (Malpetti et al, 2020(Malpetti et al, , 2021.…”
Section: Translocator Proteinmentioning
confidence: 99%
“…In preclinical TSPO imaging studies, no evidence with respect to rs6971 polymorphisms has been reported. Microglia activation assessed by using [ 11 C]PK11195 PET was reported to co-localize with tau and can predict disease progression and tau accumulation assessed by [ 18 F]flortaucipir in patients with PSP ( Malpetti et al, 2020 , 2021 ). Takuwa et al (2020) demonstrated higher [ 11 C]PBB3 uptake (tau accumulation) and [ 18 F]AC-5216 (microglia activation) in rTg4510 mice at 6 month-of-age compared to wild-type littermates.…”
Section: Neuroinflammation Imagingmentioning
confidence: 99%
“…Interestingly, a hypothetical connection between COVID-19 and atypical parkinsonism can be established as well, although data on this topic are rare so far. It was demonstrated that atypical Parkinson syndromes such as multisystem atrophy and progressive supranuclear palsy are associated with microglial activation as a sign of neuroinflammation and that the microglial activation contributes to the progression of neurodegeneration [ 110 , 111 , 112 ]. Recently, it was shown that microglial activation can be visualized by PET imaging, which might function as a biomarker for tauopathies [ 113 , 114 ].…”
Section: Chaptermentioning
confidence: 99%